Transcatheter aortic valve implantation for severe aortic stenosis in dextrocardia with situs inversus using a self-expanding aortic valve. Issue 6 (June 2018) - Morita, Yuichi; Okimoto, Tomokazu; Nagamoto, Yasutsugu; Mochizuki, Shingo; Yamada, Kazunori
Abstract: Transcatheter aortic valve implantation (TAVI) has evolved into a standard therapy for aged patients with severe aortic valve stenosis who are not candidates for surgery. However, the reports about the safety of TAVI for patients with dextrocardia situs inversus are few. An 84-year-old man with dextrocardia situs inversus underwent a TAVI for severe aortic stenosis (AS) with an aortic valve area of 0.5 cm 2, and a mean pressure gradient of 46 mmHg. Preoperative computed tomography (CT) revealed an inverted (rightward) orientation of the ventricle apex as well as the great vessels. The TAVI was performed through a transfemoral approach under general anesthesia. A left and right reversed fluoroscopic image was used for the TAVI. Finally, a 26-mm CoreValve Evolut R (Medtronic, Minneapolis, MN, USA) was successfully deployed at the aortic annulus under angiographic guidance. Post-procedural transthoracic echocardiography demonstrated a well-functioning CoreValve Evolut R with a mean pressure gradient of 8 mmHg. No complications occurred during the procedure or peri-procedural period. The patient's symptoms subsequently improved from New York Heart Association class III to class I. In conclusion, a TAVI procedure was safely performed in a patient with dextrocardia situs inversus through a transfemoral approach by evaluating the anatomical details with preoperative CT. <Learning objective: Transcatheter aortic valve implantation (TAVI) has evolved into a standard therapy for aged patients with severe aortic valve stenosis who are not candidates for surgery. On the other hand, dextrocardia situs inversus is associated with a number of additional cardiac and vascular malformations. In this case, we report on a case in which a TAVI procedure was safely performed in a patient with dextrocardia situs inversus through a transfemoral approach.>